Understanding organizational change - Helms-Mills, Jean (Routledge, 2009)
Suitable for students of organizational behaviour, organizational change, strategy and HRM, this book presents a view, which raises questions about the imperative of change, who's interests are being served, how change programmes impact on employees and why organizations continually engage in such programmes.